Immunocytes Mediate the Effects of Gut Microbiome on Inflammatory Bowel Disease: Insights From a Mendelian Randomization Study - Linbin He; Jianhui Wei; Ziye Li; Suyan Guo; Shanyu Lin; Tingting Wang; Lizhang Chen (Mediators of Inflammation)
Observational evidence suggests a complex link between gut microbiota and inflammatory bowel disease (IBD). However, the mechanisms underlying this relationship remain unclear. The present Mendelian randomization (MR) study aims to examine the causal relationships between gut microbiome and IBD (including its subtypes), and to explore potential mediating effects of immunocyte. This MR study utilized the latest genome-wide association study data, which includes 412 gut microbiome features from the Dutch Microbiome Project, a meta-analysis of 731 immunocyte traits, and summary data on IBD from the FinnGen database. The two-sample MR was employed to examine the causal associations, with inverse-variance weighted (IVW) as the main statistical method. In addition, two-step MR was used to explore the mediation effect. Our MR analysis identified the causal effects of 13 microbial taxa, 23 microbial-related functional pathways, and 27 immunocyte traits on IBD. Notably, the dTDP-L-rhamnose biosynthesis pathway is the most significant risk factor for both IBD and its subtypes. After rigorous screening, 10 combinations were examined for mediated effects. This study brings valuable evidence for the relationship between gut microbiome and IBD and the mediating role of immunocyte, providing new insights into the identification of biomarkers and interventional targets for IBD.